THE IMPORTANCE OF TORCH INFECTION IN PATIENTS OF FERTILE AGE - Berdiyarova Shokhida Shukurullaevna; Najmiddinova Nigora Kamoliddinovna; Egamberdieva Jamila Umurzoq kizi; Mustapaeva Diyora Olmosovna (Web of Journals Publishing, 2025)
TORCH infections (Toxoplasma gondii, other infections [including syphilis, varicella zoster virus, parvovirus B19], rubella, cytomegalovirus, and herpes simplex virus) are a group of pathogens capable of causing serious complications when infected during pregnancy. In patients of fertile age, especially women, timely diagnosis and prevention of TORCH infections are crucial to prevent intrauterine transmission and the development of birth defects in the fetus. This article examines the epidemiological features of TORCH infections, the mechanisms of their impact on reproductive health, modern approaches to screening and treatment, as well as the importance of an interdisciplinary approach to the management of patients planning pregnancy. The emphasis is placed on the need to include screening for TORCH infection in pre-pregnancy training and educational programs for people of reproductive age.
Keywords: TORCH infections, fertile age, reproductive health, congenital infections, pregnancy planning, prevention, screening, perinatal complications.